Anisotropic characteristics of low-rank coal fractures in the Fukang mining area, China. (1st January 2018) - Wang, Zhenzhi; Pan, Jienan; Hou, Quanlin; Yu, Bensheng; Li, Meng; Niu, Qinghe
Highlights: Fractures in different bedding plane directions were quantitatively studied. The permeability in different direction were compared and discussed. The parallel bedding plane direction fracture density and connectivity were higher. The exogenetic fracture roughness is greater than cleat. Abstract: Fractures are the main migration pathways for Coalbed Methane (CBM) in coals, which dominate the permeability of coal reservoirs. One significant anisotropic characteristic of coal is the permeability difference in the parallel and vertical bedding plane directions. Investigating the fracture characteristics in different orientations is an interesting and meaningful issue to understand the genetic mechanism of permeability contrast. This work quantitatively studied the fracture structure characteristics in different directions through the given parameters of Fukang mining area, China. The aperture, porosity, density and connectivity of coal fractures ratio in parallel bedding plane direction are 1.31, 1.12, 1.61 and 1.26 times of that in vertical direction. The main findings through the fractal calculation of fracture on end plane were draw as followings: the roughness in parallel bedding plane direction is less than that in vertical direction; the roughness of the exogenetic fracture is greater than that of cleat; there is a positive correlation between the cleat roughness and aperture; the roughness of shear fracture exceeds the roughness of tensile fracture. Additionally, the causes of fracture development discrepancies in different bedding plane directions were investigated from the perspective of the tectonic evolution history in Fukang mining area. The ratio of the fracture aperture in different bedding plane directions increases linearly with the increasing of the reservoir pressure by comparative analysis. The coal reservoir permeability in parallel bedding plane direction is 1.33–12.91 larger than that in vertical direction according to Darcy's law and the plate law. This research gives clearer insight for the heterogeneous fracture and anisotropic seepage, and provides potential theoretical guidance of CBM numerical simulation in Fukang mining area, China.